Cell-laden four-dimensional bioprinting using near-infrared-triggered shape-morphing alginate/polydopamine bioinks. (13th September 2019) - Luo, Yongxiang; Lin, Xin; Chen, Birui; Wei, Xiaoyue
Abstract: Four-dimensional (4D) bioprinting of cell-laden constructs with programmable shape-morphing structures has gained increasing attention in the field of biofabrication and tissue engineering. Currently, most of the widely used materials for 4D printing, including N -isopropylacrylamide-based polymers, are not commonly used in bioinks for cell-laden bioprinting. Herein, we propose a facile approach to create cell-laden constructs with near-infrared (NIR)-triggered shape morphing using bioinks based on alginate (the most widely used bioink for cell-laden bioprinting). Three-dimensional (3D) printed bilayered scaffolds with orthogonal structures using concentrated alginate/polydopamine (PDA) inks (14–18 wt%) showed a change in folded shape during NIR-induced dehydration. The deformation angle of the scaffold could be controlled by laser power, irradiation time and the designed patterns of the printed alginate/PDA struts in scaffolds. Then, 3D printed biphasic scaffolds consisting of alginate/PDA and cell-laden hydrogels exhibited programmable shape change under NIR stimulation. Scaffolds were able to maintain their deformed structures, and the printed cells in hydrogels retained high viability during culture in medium for at least 14 days. The biocompatible and commonly used hydrogel bioinks, NIR-triggered shape-morphing structures and maintenance of the deformed shape in the medium give this facile approach great potential for application in the field of 4D bioprinting and 4D biofabrication of artificial tissues and organs.